A Series of Dinuclear Copper Complexes Bridged by Phosphanylbipyridine Ligands: Synthesis, Structural Characterization and Electrochemistry. Issue 22 (25th January 2013) - Lilio, Alyssia M.; Grice, Kyle A.; Kubiak, Clifford P.
Abstract: The phosphanylbipyridine ligands 6‐(diphenylphosphanyl)‐4, 4′‐dimethyl‐2, 2′‐bipyridine (PPh2 ‐Me2 ‐bipy, a ), 4, 4′‐di‐ tert ‐butyl‐6‐(diphenylphosphanyl)‐2, 2′‐bipyridine (PPh2 ‐ t Bu2 ‐bipy, b ), and 6‐(diisopropylphosphanyl)‐2, 2′‐bipyridine (P i Pr2 bipy, c ) and the corresponding dinuclear copper complexes [Cu2 (μ‐PPh2 ‐Me2 ‐bipy)2 (NCCH3 )2 ](PF6 )2 (1 ), [Cu2 (μ‐PPh2 ‐ t Bu2 ‐bipy)2 (NCCH3 )2 ](PF6 )2 (2 ), [Cu2 (μ‐P i Pr2 bipy)2 (μ‐NCCH3 )](PF6 )2 (3 ), and [Cu2 (μ‐P i Pr2 bipy)2 {μ‐CNCH(CH3 )2 }](PF6 )2 (4 ) were synthesized. The X‐ray structures of1 –4 show that the complexes are dinuclear with the bidentate bipyridine coordinating to one copper atom and the phosphane moiety coordinating the other copper center. Complexes3 and4 possess short Cu–Cu distances with bridging acetonitrile and isocyanide ligands. The cyclic voltammograms of1 –4 were examined under N2 and CO2 . Under N2, 1 –3 show four quasi‐reversible 1e – reductions, and under CO2, they show current enhancement at the second reduction. In comparison, complex4 shows four irreversible reductions under N2 and no current enhancement under CO2 . Abstract : Three phosphanylbipyridine ligands that react with Cu I to form dimeric complexes have been synthesized and structurally characterized. The Cu–Cu distance can be controlled by ligand substitution, and electrochemical studies of the dimers suggest that four sequential 1e – reductions of the bipyridine ligands occur. Catalytic behavior is observed under CO2 .